2022
DOI: 10.1159/000523937
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic Novel USP53 Splicing Variant Disrupting the Gene Function that Causes Cholestasis Phenotype and Review of the Literature

Abstract: <b><i>Introduction:</i></b> Hereditary cholestasis is a heterogeneous group of liver diseases that mostly show autosomal recessive inheritance. The phenotype of cholestasis is highly variable. Molecular genetic testing offers an useful approach to differentiate different types of cholestasis because some symptoms and findings overlap. Biallelic variants in <i>USP53</i> have recently been reported in cholestasis phenotype. <b><i>Methods:</i></b> In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…USP53, a member of ubiquitin specific proteases involved in deconjugation of ubiquitin and ubiquitin-like protein adducts, is a cysteine protease with complex organizational structures and different functional properties. 8 In animal models, it has been shown that USP53 is a component of the tight junction complex. 9 13 Tight-junction-associated proteins are involved in the survival of auditory hair cells and hearing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…USP53, a member of ubiquitin specific proteases involved in deconjugation of ubiquitin and ubiquitin-like protein adducts, is a cysteine protease with complex organizational structures and different functional properties. 8 In animal models, it has been shown that USP53 is a component of the tight junction complex. 9 13 Tight-junction-associated proteins are involved in the survival of auditory hair cells and hearing.…”
Section: Discussionmentioning
confidence: 99%
“… 6 13 In humans, USP53 has critical roles in many important processes, especially substance transport, membrane permeability, membrane stability, apoptotic processes, repair, and regulation at the transcriptional/translational level. 8 15 The C-terminal domain of USP53 can interact with the tight junction protein 1 (TJP1) and TJP2 heterodimer associated with cholestasis risk. 3 8 16 A total of 19 different USP53 mutations have been reported, including six frameshift mutations, five nonsense mutations, four missense mutations, two indel mutations, one mutation in splicing site, and one small deletion ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hereditary cholestasis [74,75] Progressive hearing loss [76] CYLD Crohn disease [50] Growth arrest is required for cells to undergo differentiation. 83 However, USP7 overexpression increased cell proliferation, which may be the reason that overexpressed USP7 did not enhance the differentiation of the BMSCs.…”
Section: Usp53mentioning
confidence: 99%
“…USP53 (ubiquitin specific peptidase 53) spliceosome variants can result in the premature termination of the protein, leading to the loss of its functional structure and abnormal metabolic and regulatory interactions. This can contribute to cholestasis in affected individuals ( Gezdirici et al, 2023 ). Jing Zhang et al did discover that USP53 mutations may play a role in some of the phenotypic features observed in cases of TJP2 defect ( Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%